Rational Primer and Probe Construction in PCR-Based Assays for the Efficient Diagnosis of Drifting Variants of SARS-CoV-2 - Divya RSJB Rana; Nischal Pokhrel; Santosh Dulal (Advances in Virology)
The genome sequence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been evolving via genomic drifts resulting in “emerging/drifting variants” circulating worldwide. The construction of polymerase chain reaction (PCR) assays for the reliable, efficient, and specific diagnosis of the drifting variants of SARS-CoV-2 is specifically governed by the selection and construction of primers and probes. The efficiency of molecular diagnosis is impacted by the identity/homology of the genome sequence of SARS-CoV-2 with other coronaviruses, drifting variants or variants of concern (VOCs) circulating in communities, inherent capacity of mutation(s) of various target genes of SARS-CoV-2, and concentration of genes of interest in host cells. The precise amplicon selection and construction of primers and probes for PCR-based assays can efficiently discriminate specific SARS-CoV-2 drifting variants. The construction of single nucleotide polymorphism (SNP)-specific primers and probes for PCR assays is pivotal to specifically distinguish SARS-CoV-2 variants present in the communities and contributes to better diagnosis and prevention of the ongoing COVID-19 pandemic. In this study, we have utilized in silico-based bioinformatic tools where the alignment for genes, the positions and types of SNPs/mutations of VOCs, and the relative number of SNPs per nucleotide in different genomic regions were investigated. Optimal and specific genome region (amplicon) selection with comparatively lower mutability in the SARS-CoV-2 genome should be prioritized to design/construct PCR assays for reliable and consistent diagnosis in various regions of the world for a longer duration of time. Further, the rational selection of target genes that is at an optimal detectable concentration in biological samples can bolster PCR assays of high analytical sensitivity. Hence, the construction of primers and probes with the rational selection of targeting specific E gene, genomic regions with highly conserved sequences, multiple target genes with relatively lower mutability and detectable level of concentration, SNP-specific binding regions of spike (S gene) protein, and shorter amplicon size (100–150 bp) are vital for the PCR assays to achieve optimal efficiency in the point-of-care laboratory diagnosis of circulating drifting variants of SARS-CoV-2 with optimal accuracy.